Too much and never enough : [compact disc, unabridged] : how my family created the world's most dangerous man - Trump, Mary L. (Simon & Schuster Audio, 2020)
In this revelatory, authoritative portrait of Donald J. Trump and the toxic family that made him, Mary L. Trump, a trained clinical psychologist and Donald's only niece, shines a bright light on the dark history of their family in order to explain how her uncle became the man who now threatens the world's health, economic security, and social fabric.